An androgen reduced transcript of LncRNA GAS5 promoted prostate cancer proliferation. - Yingyi Zhang; Xinya Su; Zhe Kong; Fangqiu Fu; Pu Zhang; Dan Wang; Hai Wu; Xuechao Wan; Yao Li (PLoS ONE)
Prostate cancer (PCa) becomes a leading cause of death in males nowadays. Recent reports showed that androgen-responsive long non-coding RNAs played important roles in tumorigenesis and progression of PCa. In this study, we focused on a special transcript of GAS5 (ENST00000456293.5, GAS5-007), which was reported as a tumor suppressor. Here, we demonstrated GAS5-007 was reduced by androgen treatment and inhibited by AR. Next, we explored the expression level of GAS, finding the expression of it in PCa tissue was higher than normal tissue in both public databases and human tissue samples. Functional analysis of GAS5 showed it was related to regulating translational elongation, protein biosynthesis, and transcription. Moreover, we observed GAS5-007 knockdown inhibited the proliferation, cell cycle and promoted cell apoptosis of PCa. We also constructed a GAS5-miRNA network to explain the different roles of different GAS5 transcripts in PCa. This study provides novel insights to identify potential diagnostic biomarker and therapy target for prostate cancer in clinical treatment.